Determination of indications for the transition to restrictive tactics of infusion therapy in critically ill preterm infants in the early neonatal period - P. I. Mironov; Yu. S. Aleksandrovich; R. G. Idrisova; E. D. Galimova; E. I. Gilmanova; R. Z. Bogdanova (Вестник анестезиологии и реаниматологии)
Introduction. To date, reliable information about the “ideal” infusion therapy regimen for critically ill preterm infants in the early neonatal period is not known.The objective was to determine the indications for the transition to restrictive tactics of infusion therapy in critically ill preterm infantsMaterials and methods. The design was a prospective, observational study. The development included 110 newborns < 32 weeks of gestation (birth weight less than 1500 grams). 11 of them died.Results. In deceased newborns, right ventricular mean pressure (RVMP) was higher in the first 3 days of intensive care and the left ventricular ejection fraction (LVEF) was higher by the third day of treatment they had a higher vasoactive inotropic index. The critical threshold value of RVMP was 29.0 mmHg. The “separation point” regarding the risk of death depending on the volume of infusion therapy was 100 ml/kg/day. The threshold value of the nSOFA score regarding the need to limit the volume of infusion therapy based on ROC analysis was 5.0 points.Conclusion. Preterm infants with a high risk of death (nSOFA score > 5 points) require restrictive infusion therapy. The critical threshold value for the volume of fluid administered may be 100 ml/kg/day.